A Cross-Cultural Study of Values Emphasized in Education - Sood, James (International journal of value-based management, 1998)
The study involves an analytical investigation of the relative importance of eighteen values in the education of young people in nine countries. While the difficulties in obtaining the data led to numerous limitations, the indications developed in the analysis provide an interesting comparison of the similarities and differences in a number of very different cultures. The study also demonstrates an analytical direction that could provide a useful method for comparing different cultures.